ULTRASTRUCTURAL ANALYSIS OF THE GAP JUNCTIONS BETWEEN RAT’S VENTRICULAR CARDIOMYOCYTES AFTER CHRONIC PRENATAL HYPOXIA INFLUENCE - Petruk, N.S. (World of Medicine and Biology, 2014)
We have conducted ultrastructural analysis and distribution of the gap junctions in the rat’s ventricles at the 1st, 3rd, 7th, 14th, 30th days during postnatal ontogeny and among mature animals in the normal and after the chronic fetal hypoxia. The control group was intact healthy animals and in the experimental group were animals,which exposed chronic prenatal hypoxia. We found that there are: retention of redistribution of the gap junctions from the lateral surface of the cell to the area of the intercalated disks, reduction of the total length functionally active gap junctions, and the presence of the lateral gap junctions in the adult ventricular myocardium in experimental group of rats.
Keywords: rats; ventricular myocardium; postnatal ontogenesis; prenatal hypoxia; annular gap junction